2011
DOI: 10.1002/bies.201000121
|View full text |Cite
|
Sign up to set email alerts
|

The sweet connection: Solving the riddle of multiple sugar‐binding fimbrial adhesins in Escherichia coli

Abstract: Proteinaceous stalks produced by Gram-negative bacteria are often used to adhere to environmental surfaces. Among them, chaperone-usher (CU) fimbriae adhesins, related to prototypical type 1 fimbriae, interact in highly specific ways with different ligands at different stages of bacterial infection or surface colonisation. Recent analyses revealed a large number of potential and often "cryptic" CU fimbriae homologues in the genome of commensal and pathogenic Escherichia coli and closely related bacteria. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 107 publications
2
58
0
Order By: Relevance
“…A fragment of 1,588 bp was obtained by merging the two sequences, and blastn analysis indicated that it shares identity with cshB and faeD genes, encoding usher proteins involved in assembly of K88-related fimbriae. The prototype members of the K88 or F4 fimbriae were first identified in ETEC strains that infect pigs (16). Amino acid sequences derived from both genes did not contain the peptide sequence found in the AalE N terminus (TV NGDGGSV), suggesting that the identified novel putative usher protein is involved in the export of AalE to the bacterial surface.…”
Section: Resultsmentioning
confidence: 99%
“…A fragment of 1,588 bp was obtained by merging the two sequences, and blastn analysis indicated that it shares identity with cshB and faeD genes, encoding usher proteins involved in assembly of K88-related fimbriae. The prototype members of the K88 or F4 fimbriae were first identified in ETEC strains that infect pigs (16). Amino acid sequences derived from both genes did not contain the peptide sequence found in the AalE N terminus (TV NGDGGSV), suggesting that the identified novel putative usher protein is involved in the export of AalE to the bacterial surface.…”
Section: Resultsmentioning
confidence: 99%
“…The main limitation of this approach is the multiplicity of structures involved in bacterial adhesion. However, one way to circumvent this issue is to use multivalent inhibitors linked to a scaffold of glycopolymers, glyconanoparticles that may permit inhibition of several adhesins at the same time (279)(280)(281).…”
Section: Targeting Biofilm Recalcitrance: Progress and Perspectivesmentioning
confidence: 99%
“…Systematic studies have addressed this for bacteria such as E. coli and S. enterica, showing that while some fimbriae do not seem to have a role or to even be expressed under standard in vitro growth conditions, others are required at different levels to establish bacterial interactions with different biotic or abiotic surfaces and receptors, leading to cell adherence, colonization of different host tissues or environmental reservoirs, interactions between bacterial cells, biofilm formation, and pathogenesis (31,(34)(35)(36). Moreover, there is still much to learn about their specific expression patterns and the regulatory mechanisms coordinating their expression in response to the environment and the host (30).…”
Section: Discussionmentioning
confidence: 99%